Genome-Wide Identification and Expression Analysis of the 14-3-3 Family Genes in Medicago truncatula - Qin, Cheng; Cheng, Linming; Shen, Jingqin; Zhang, Yunhong; Cao, Huimin; Lu, Dan; Shen, Chenjia (Frontiers in Plant Science, 2016)
The 14-3-3 gene family, which is conserved in eukaryotes, is involved in protein-protein interactions and mediates signal transduction. However, detailed investigations of the 14-3-3 gene family in Medicago truncatula are largely unknown. In this study, the identification and study of M. truncatula 14-3-3-family genes were performed based on the latest M. truncatula genome. In the M. truncatula genome, 10 14-3-3 family genes were identified, and they can be grouped into ε and non-ε groups. An exon-intron analysis showed that the gene structures are conserved in the same group. The protein structure analysis showed that 14-3-3 proteins in M. truncatula are composed of nine typical antiparallel α-helices. The expression patterns of Mt14-3-3 genes indicated that they are expressed in all tissues. Furthermore, the gene expression levels of Mt14-3-3 under hormone treatment and Sinorhizobium meliloti infection showed that the Mt14-3-3 genes were involve in nodule formation. Our findings lay a solid foundation for further functional studies of 14-3-3 in M. truncatula.